Trajetórias socioespaciais, narrativas cinematográficas e lazer de cineastas negras: intersecções entre racismo e sexismo - Iara Félix Pires Viana (2021)
This work aims to join research that has sought to reflect on race relations in Brazilian society and the implications in the academic and artistic fields, the latter being considered explicitly in audiovisual production. The general objective is to discuss intersections of gender and race in the socio-spatial trajectories of black filmmakers. The specific ones are to understand: a) the perception of black filmmakers about epistemic racism and sexism in their trajectories and their audiovisual productions. b) the (im)possible/existent negotiations between black autonomous authorial creation and the racialized political, epistemological, and ontological contexts of this production. The research is based on the contributions of decolonial studies, leisure studies, feminist criticism, film theory, and black feminism about the intersections of racism and sexism, assuming the place of speech as a political act. Of a qualitative nature, with the technique of in-depth interviews, the raw material of this investigative construction is composed of the socio-spatial trajectories of seven black women filmmakers. For the organization and systematization of the results, the Discourse of the Collective Subject (DSC), technique was used through the Qualiquantisoft software, which can work with selected samples of individuals, segmenting or filtering the results anchorages and critical ideas. Six categories of analysis were defined: first) self-representation/intersectionality(s); second) decolonial black feminism; third) epistemic racism/memoricide; fourth) black cinema; fifth) aquilombing/black educator movement and sixth) the leisure of black humanity. The analysis was conducted based on the concept of feminine and black socio-spatiality and delineated from the dislocations of being a black woman to being a black woman filmmaker. Considering the role of cinema as a product and producer of imaginary, we verified in this discourses analysis the collective subjects, the transits, and spatial, social, and symbolic displacements on which the intersection of racism, sexism, and social inequality incurs. Although the capacity for agency, creative strategies of (re)existence in the narrative construction, and the elements of audiovisual language emerge, which go through epistemic racism, the Black Educator Movement, and the political and affirmative definition of what today is called Black cinema. In this thesis, due to the racialized context research, a transcendental movement was constructed to add a new conception of leisure, named unsubmissive leisure. It is leisure that welcomes black bodies as humans. Thus, the multidimensionality of cinematic leisure is configured in this study as dialogic, characterized as holding a political, ethical, aesthetic, and affirmative storyline. It is hoped to encourage future research in the broad area of knowledge production in Leisure Studies, Cinema, and Education, interrogating and valuing multiplicity and intersectionality.